Extensive legal exceptionalism, an administrative export-processing zone and urbanization in Mauritius. Issue 2 (4th May 2018) - Dirksmeier, Peter
ABSTRACT: An analysis of the repercussions of the administrative Mauritian export-processing zone (EPZ), encompassing the territory of the whole main island of the Republic of Mauritius, for the trajectory of urbanization finds that unlike specific economic zones such as Shenzhen special economic zone, China, the Mauritian EPZ only had an historical impact on the urbanization of the main island. The correlates of current urbanization are unemployment, property, marginalization and foreign in-migration, reflecting general urbanization trends in the Global South. However, the island exhibits a highly fragmented urban fabric and differentiated rural areas, whose emergence is related to the history of the EPZ.